Enhanced immunosuppression improves early allograft function in a porcine kidney transplant model of donation after circulatory death. Issue 3 (26th September 2018) - Xu, Min; Garcia‐Aroz, Sandra; Banan, Babak; Wang, Xuanchuan; Rabe, Brian J.; Zhou, Fangyu; Nayak, Deepak K.; Zhang, Zhengyan; Jia, Jianluo; Upadhya, Gundumi A.; Manning, Pamela T.; Gaut, Joseph P.; et al.
Abstract : It remains controversial whether renal allografts from donation after circulatory death (DCD) have a higher risk of acute rejection (AR). In the porcine large animal kidney transplant model, we investigated the AR and function of DCD renal allografts compared to the non‐DCD renal allografts and the effects of increased immunosuppression. We found that the AR was significantly increased along with elevated MHC‐I expression in the DCD transplants receiving low‐dose immunosuppression; however, AR and renal function were significantly improved when given high‐dose immunosuppressive therapy postoperatively. Also, high‐dose immunosuppression remarkably decreased the mRNA levels of ifn‐g, il‐6, tgf‐b, il‐4, and tnf‐a in the allograft at day 5 and decreased serum cytokines levels of IFN‐g and IL‐17 at day 4 and day 5 after operation. Furthermore, Western blot analysis showed that higher immunosuppression decreased phosphorylation of signal transducer and activator of transcription 3 and nuclear factor kappa‐light‐chain‐enhancer of activated B cells‐p65, increased phosphorylation of extracellular‐signal‐regulated kinase, and reduced the expression of Bcl‐2‐associated X protein and caspase‐3 in the renal allografts. These results suggest that the DCD renal allograft seems to be more vulnerable to AR; enhanced immunosuppression reduces DCD‐associated AR and improves early allograft function in a preclinical large animal model. Abstract : Donation after cardiac death kidneys with extended warm ischemia appear to be more vulnerable to acute rejection, worsening early allograft function after transplant, which can be reduced by enhanced immunosuppression in a preclinical large animal model.